Development of non-conventional formulations of dinitroanilines for the treatment of leishmaniasis - Lopes, Rui Manuel Jesus, 1979- (2014)
Tese de doutoramento, Farmácia (Tecnologia Farmacêutica), Universidade de Lisboa, Faculdade de Farmácia, 2013